Nowotestamentalny paradoks mocnej słabości w egzegezie biblijnej Orygenesa - Szram, Mariusz (Vox Patrum, 2018)
The subject of the article is the extraction and systematization of the basic aspects of Origen’s exegesis of biblical texts on the paradox of strong weakness (Mt 5, 10-11; 2Cor 12, 8-9) and embedding them in the realities of the epoch. According to Origen all human weakness – resulting both from man’s own sins and from the oppression experienced from outside – is a situation that should be used as an opportunity to take up spiritual fight and to accept God’s power, without which man is unable to overcome any difficulties. This interpretation reflects several circumstances of that era: martyr’s piety, consisting in a desire to become like Christ suffering; the necessity of finding a theological justification for various experiences that make a person in a situation of extreme weakness, such as: persecution for faith or the practice of slavery; and finally, the conviction that the final victory is close, resulting from literally understood words of Christ about His return and the end of the world, before this generation passes away (cf. Mt 23, 34). The model of spirituality, developed on the basis of the biblical paradox of strong weakness and consisting in enduring suffering in connection with Christ and with the help of His divine power, has become an indispensable component of Christian piety also in later epochs. It could be a kind of medicine for being too attached to the own human capabilities in spiritual struggle with passions, which was the legacy of extremely conceived stoic ethics and could influence the development of later movements limiting the power of God’s grace in the fight against own weaknesses, such as Pelagianism.